New modeling approach of secondary control layer for autonomous single-phase microgrids. Issue 13 (September 2019) - Bendib, Ahmed; Chouder, Aissa; Kara, Kamel; Kherbachi, Abdelhammid; Barkat, Said; Issa, Walid
Highlights: New modeling approach of the secondary control for single-phase microgrid is proposed. SOGI-FLL dynamics are introduced in the modeling of the secondary control layer. Amplitude dynamic model of SOGI-FLL is derived based on phasor theory. Tuning procedure for the proper selection of the control parameters is discussed. The proposed control approach is tested under various disturbances. The results validate the proposed approach to achieve the desired transient response. Abstract: In a microgrid (MG) topology, the secondary control is introduced to compensate for the voltage amplitude and frequency deviations, mainly caused by the inherent characteristics of the droop control strategy. This paper proposes an accurate approach to derive small signal models of the frequency and amplitude voltage at the point of common coupling (PCC) of a single-phase MG by analyzing the dynamics of the second-order generalized integrator-based frequency-locked loop (SOGI-FLL). The frequency estimate model is then introduced in the frequency restoration control loop, while the derived model of the amplitude estimate is introduced for the voltage restoration loop. Based on the obtained models, the MG stability analysis and proposed controllers' parameters tuning are carried out. Also, this study includes the modeling and design of the synchronization control loop that enables a seamless transition from island mode to grid-connected mode operation. Simulation and practical experiments of a hierarchical control scheme, including traditional droop control and the proposed secondary control for two single-phase parallel inverters, are implemented to confirm the effectiveness and the robustness of the proposal under different operating conditions. The obtained results validate the proposed modeling approach to provide the expected transient response and disturbance rejection in the MG.